2018
DOI: 10.26508/lsa.201800107
|View full text |Cite
|
Sign up to set email alerts
|

The histone chaperone FACT modulates nucleosome structure by tethering its components

Abstract: The histone chaperone FACT functions by tethering partial components of the nucleosome, thereby assisting nucleosome disassembly and reassembly during transcription.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 46 publications
3
44
0
Order By: Relevance
“…The body of KAP1 interactors reflects its recruitment predominantly to the chromatin fraction of the nucleus. In addition to its known partners in heterochromatin formation and transcriptional silencing, such as HP1 proteins and components of the NURD complex, our analysis of the KAP1 interactome in K562 leukaemic cells identified several factors involved in modulating the structure of euchromatin and the activity of RNA polymerases [24,25,[33][34][35][36][37]. This fits with the detection by several studies including ours of KAP1 at the promoters of numerous PolII-transcribed genes.…”
Section: Discussionsupporting
confidence: 88%
“…The body of KAP1 interactors reflects its recruitment predominantly to the chromatin fraction of the nucleus. In addition to its known partners in heterochromatin formation and transcriptional silencing, such as HP1 proteins and components of the NURD complex, our analysis of the KAP1 interactome in K562 leukaemic cells identified several factors involved in modulating the structure of euchromatin and the activity of RNA polymerases [24,25,[33][34][35][36][37]. This fits with the detection by several studies including ours of KAP1 at the promoters of numerous PolII-transcribed genes.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with a role in transcription, FACT occupancy is generally proportional to the level of transcription (Mason and Struhl 2003;Pelechano et al 2009;Mayer et al 2010;Feng et al 2016). However, this occupancy profile can also be explained by a more passive model in which FACT localization is driven by exposure of its binding sites during any process that disrupts nucleosomes, including transcription (Kemble et al 2015;Tsunaka et al 2016;Martin et al 2018;Wang et al 2018). In this model, FACT's role is to rescue disrupted nucleosomes by reversing the reorganization pathway.…”
mentioning
confidence: 97%
“…Strains with mutations affecting Mcm2 histone-binding residues suffered from a loss of heterochromatin, highlighting its importance in histone recycling. Crystallography and single molecule assays using optical tweezers show that the SUPT16H subunit of FACT (Spt16 in yeast) can displace and tether nucleosomal H2A-H2B dimers while stabilizing the (H3-H4) 2 tetramer (Chen P. et al, 2018;Wang et al, 2018;Liu et al, 2020). Further structural work showed that MCM2 in turn associates with (H3-H4) 2 surfaces that normally interact with DNA, thereby shielding the tetramer from aberrant interactions (Huang et al, 2015b).…”
Section: Histone Recycling and Tools To Study Interactions At Replicamentioning
confidence: 99%
“…It is, however, important to emphasize that the histone chaperone has since been implicated in numerous other biological events (Gurova et al, 2018). Although first described as an H2A-H2B histone chaperone, it can also bind histones H3 and H4 (Martin et al, 2018;Wang et al, 2018;Mayanagi et al, 2019). FACT allows a controlled assembly and disassembly of nucleosomes in vitro.…”
Section: Histone Dynamics During Gene Transcriptionmentioning
confidence: 99%